PERDAGANGAN ILEGAL PENYU SISIK (ERETMOCHELYS IMBRICATA) DI KALIMANTAN TIMUR BERDASARKAN CITES 1973: Illegal Trade of Hawksbill Turtles (Eretmochelys Imbricata) in East Kalimantan Based on CITES 1973 - Fiona Fatianisa; Amalia Zuhra (Faculty of Law, Universitas Trisakti, 2025)
The illegal trade of hawksbill turtles is an act prohibited by the CITES Convention of 1973. This Convention aims to protect threatened wildlife and biodiversity. The illicit trade of hawksbill turtles in East Kalimantan warrants serious attention due to the declining population of hawksbill turtles, which is deemed a violation of regulations. The issue revolves around the effectiveness of law enforcement against the illegal trade of hawksbill turtles in East Kalimantan based on the CITES Convention of 1973 and Indonesia’s responsibility in the case of unlawful hawksbill turtle trade in East Kalimantan under the Convention. This research adopts a normative legal research approach, with a descriptive nature and deductive reasoning to conclude. The result and conclution of the article that activities are illegal because the trade of hawksbill turtles is only permitted for scientific research purposes. This action highlights Indonesia’s need to enforce laws and impose sanctions on offenders in line with legal provisions. Indonesia holds strict liability due to proven negligence and must provide restitution as a form of compensation.